Brain-inspired computing needs a master plan - Mehonic, A.; Kenyon, A. J. (Nature (London), 2022)
New computing technologies inspired by the brain promise fundamentally different ways to process information with extreme energy efficiency and the ability to handle the avalanche of unstructured and noisy data that we are generating at an ever-increasing rate. To realize this promise requires a brave and coordinated plan to bring together disparate research communities and to provide them with the funding, focus and support needed. We have done this in the past with digital technologies; we are in the process of doing it with quantum technologies; can we now do it for brain-inspired computing? The benefits and future prospects of neuromorphic, or bio-inspired, computing technologies are discussed, as is the need for a global, coordinated approach to funding, research and collaboration.